Compatibilized PP/EPDM-kenaf fibre composite using melt blending method - Anuar, Hazleen; Hassan, N. A.; Mohd Fauzey, F. (Trans Tech Publications, Switzerland, 2011)
Thermoplastic Elastomer (TPE) composite reinforced with Hibiscus cannabinus, L fiber (kenaf fiber, KF) was prepared via melt blending method using internal mixer at temperature 180